(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Leptospirosis, a zoonotic disease is increasingly being recognized in developing countries. It is often underdiagnosed resulting in significant mortality as the presenting features mimic other commonly prevailing diseases like Malaria, Dengue, Acute hepatitis, Typhoid in developing world. We report a case of 32 yrs old male, sewer worker presented with acute febrile illness with icterus, hemorrhagic manifestation and pulmonary-renal involvement, diagnosed as Severe Leptospirosis (Weils disease) confirmed by ICT method. This experience highlights the importance of considering Leptospirosis early in the diagnosis of acute non specific febrile illness with multi-organ involvement to cutoff mortality from this fatal disease. Chatt Maa Shi Hosp Med Coll J; Vol.15 (2); Jul 2016; Page 61-64